MITIGASI BENCANA BERBASIS BUDAYA LOKAL: ADAPTASI KOMUNITAS DESA TEMPUR TERHADAP BENCANA BANJIR - Vega Ariyanti; Binta Atiul Azka; Dany Miftah M. Nur (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study aims to identify and analyze local wisdom-based mitigation practices carried out by the Tempur Village community, Keling District, Jepara Regency, in responding to the threat of floods and landslides. Using a qualitative descriptive approach with a case study design, data were obtained through direct observation techniques, in-depth interviews, and archival documentation. The findings show that local communities utilize a combination of traditional knowledge, cultural values, and collective social practices as adaptive strategies for disasters. These forms of local wisdom include arranging settlements in highland areas, protecting forest areas as natural fortresses, and utilizing environmental signs as early warnings of disasters. Communal values ​​such as togetherness, deliberation, and traditional rituals such as sedekah bumi help strengthen the community's social resilience in dealing with emergency situations. This approach has proven to be quite effective in reducing the negative impacts of disasters, as indicated by the low level of damage and loss of life when a disaster occurs. However, there are challenges in terms of passing on this wisdom to the younger generation, as well as the lack of documentation of existing local practices. Therefore, strong collaboration is needed between the government, community, and educational institutions to maintain, revitalize, and integrate local wisdom into a more sustainable disaster mitigation system.